Innovation Elements, Incubation Capacity, and Incubation Performance in Biomedical Incubation Platforms: Moderating Role of Customized Services - Jiang, Qian; Wang, Dan; Wang, Yunfeng; Wu, Bingye (Frontiers in Public Health, 2022)
Biomedical incubation platform makes full use of innovation elements, constantly absorbs, integrates and allocates various resources, and innovates the incubation service mode, which is an important path to improve the performance of innovation incubation. Based on resource-based theory, network theory and value chain theory, we proposed the conceptual model and research hypothesis of the relationship between innovation elements, incubation capacity and innovation incubation performance in biomedical incubation platform, and the customized service is discussed as a moderating variable. The empirical results show that innovation elements have a significant positive impact on the improvement and transition of incubation capacity, incubation capacity has a significant positive impact on innovation incubation performance in biomedical incubation platform, and customized service plays a significant positive regulatory role between incubation capacity and innovation incubation performance in biomedical incubation platform.